PEDAGOGICAL SUPPORT OF STUDENTS’ PROFESSIONAL SELF-DETERMINATION IN HIGHER EDUCATION - Vyacheslav A. Starodubtsev; Mikhail A. Solov’Ev; Elena Yu. Valitova (Высшее образование в России)
The article discusses the organizational and pedagogical conditions that support professional development of engineering universities students as a part of the individualized and personalized educational process. The article shows the need to introduce into curricula special disciplines trades to acquaint students with the specific of engineering professions and to teach them the technology of career development. Special attention is paid to the problem of students’ professional selfHdetermination as a lifelong process of professional development. The authors reveal the difference between the notions “individualization”, “personification”, and “personalization” as applied to the activities of a lecturer and a student.